Meningkatkan Pemahaman Guru Sekolah Dasar Melalui Pelatihan Penyusunan Rencana Pelaksanaan Pembelajaran Berbasis Literasi, 4C, PPK dan Hots - Handayani, Sri Lestari; Amirullah, Gufron (Jurnal SOLMA, 2019)
One of the problem was experienced by teachers in SDN Kebon Pala 12 and 13 Pagi is the ability of teachers in preparing lesson plan based on literacy, 4C, PPK and HOTS is still lacking. The target of this activity was the implementation of training activity of lesson plan preparation based on literacy, 4C, PPK, and HOTS for teacher of 1st and 4th grade in Gugus Agus Salim. This method was in the form of training that is intended for elementary school teachers. Data collection techniques in this activity were documentation, interviews, and tests. The data were analyzed using t test and normalized gain test. Based on the results of the two-tail t test and the gain test were indicate that the implementation of this training has an effect in improving the knowledge of the teachers understanding about K13 and how to set up the learning tool, especially the preparation of lesson plan based on literacy, 4C, PPK, and HOTS.